Decolorization of Reactive Black 5 by Myceliophthora thermophila KLUM1 - Susanti, Evi; Jati, Rizky Febriani; Apriani, Dwi; Suharti, Suharti; Alvionita, Mieke (Department of Chemistry, Faculty of Science and Technology Syarif Hidayatullah Jakarta State Islamic University, 2025)
This research aimed to ascertain the impact of alkaline lignin of teak sawdust on the synthesis of ligninase and decolorization of Reactive Black 5 (RB5) by M. thermophilia KLUM1, also to elucidate the mechanism of mycoremediation. This research was conducted within the cultivation of the spore suspension in a co-culture setting. The RB5 dye percentage decolorization and ligninase activity were produced by varying the addition of alkaline lignin. The results show that the addition of 0.5% alkaline lignin accelerates the production of ligninase in the Kirk medium. However, adding more than 0.5% alkaline lignin does not affect the highest amount of ligninase produced. The increase in RB5 dye decolorization by M. thermophila KLUM1 is proportional to the increase in alkaline lignin in the medium. The percentage of wood-rot fungi decolorization in Kirk medium with and without lignin with the addition of 0.5%, 1%, and 2% lignin on the 10th day was 26.29%, 29.51%, 34.74%, and 40.43%, respectively. The decolorization process of RB5 by M. thermophilia KLUM1 in Kirk medium with alkaline lignin occurs through several mechanisms, i.e., enzymatic degradation, adsorption by the growing mycelia, and alkaline lignin present in the medium.